Covalent three-dimensional networks of graphene and carbon nanotubes: synthesis and environmental applications. (February 2017) - Dasgupta, Archi; Rajukumar, Lakshmy Pulickal; Rotella, Christopher; Lei, Yu; Terrones, Mauricio
Graphical abstract: Highlights: The great potential of covalent three-dimensional networks of graphene and CNTs in environmental applications is presented. State of the art synthetic and processing methods for these 3D networks, their doped analogues and composite structures with transition metal dichalcogenides are discussed. Theoretically and experimentally obtained physical properties of these 3D networks relevant to environmental applications are highlighted. Aqueous and gas phase adsorption of environmental pollutants and their catalytic conversion on 3D graphene/CNT networks are discussed. Applications of 3D graphene/CNT networks for alternative energy applications are briefly mentioned. Abstract: In recent years tremendous efforts have been made to exploit the exceptional properties of 1-Dimensional carbon nanotubes and 2-Dimensional graphene in order to interconnect those forming 3-Dimensional hybrid systems. Such macroscopic 3-D networks possess several advantages such as highly accessible surface area, minimized agglomeration or re-stacking, enhanced thermal and electrical transport, and robust mechanical properties as compared to their nanoscale 1-D or 2-D building blocks. This review aims to provide a fundamental understanding of state-of-the-art synthesis methodologies for interconnecting these carbon nanostructures, structure-property relationships as well as potential environmental applications related to adsorption, catalysis, sensing, and energy conversion. The technical challenges and future research opportunities are also discussed.